2023
DOI: 10.3390/plants12132404
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Transcriptional, Metabolic, and Physiological Responses to Drought Stress in Ilex paraguariensis Roots

Abstract: The appearance of water stress episodes triggers leaf abscission and decreases Ilex paraguariensis yield. To explore the mechanisms that allow it to overcome dehydration, we investigated how the root gene expression varied between water-stressed and non-stressed plants and how the modulation of gene expression was linked to metabolite composition and physiological status. After water deprivation, 5160 differentially expressed transcripts were obtained through RNA-seq. The functional enrichment of induced trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…In addition, AhNCED1 contains two MeJA elements and one SA element, while AhNCED2 contains one SA element (Table S2). ABA can interact with hormones such as MeJA and SA [16]. Therefore, the expression levels of AhNCED1 and AhNCED2 were significantly upregulated under 20% PEG6000-induced drought stress in the NH5 (drought-tolerant) and FH18 (drought-sensitive) cultivars (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AhNCED1 contains two MeJA elements and one SA element, while AhNCED2 contains one SA element (Table S2). ABA can interact with hormones such as MeJA and SA [16]. Therefore, the expression levels of AhNCED1 and AhNCED2 were significantly upregulated under 20% PEG6000-induced drought stress in the NH5 (drought-tolerant) and FH18 (drought-sensitive) cultivars (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term studies have shown that the endogenous hormone abscisic acid (ABA) is intricately linked to regulating drought resistance in some plants [7][8][9][10][11][12]. Furthermore, in some plants, NCED genes related to ABA synthesis were critical involvement in drought resistance mechanisms [13][14][15][16]. For instance, the overexpression of OsNCED5 in Oryza sativa has been shown to increase ABA levels, enhance tolerance to drought stress, and accelerate leaf senescence [14].…”
Section: Introductionmentioning
confidence: 99%